Peran Camat dalam Penertiban Pasar Liar di Desa Lalang Kecamatan Sunggal Kabupaten Deli Serdang - Muhammad Nurdin; Adam Adam; Budi Hartono (Universitas Medan Area, 2021)
The responsibility for controlling the weeds is in the hands of the Sunggal sub-district, where the sub-district also collects retribution from the traders in accordance with the sub-district regulations. However, with the emergence of various problems from the existence of the illegal market, it becomes an illustration that the sub-district head is still not playing a role in managing the illegal market in his area, thus becoming a source of disturbance for other road users. The purpose of the study was to determine the role of the Camat in controlling the illegal market in Lalang Village, Sunggal District, Deli Serdang Regency. The benefits of research to add insight and knowledge in the field of controlling illegal markets. This research is a qualitative research in which researchers go directly to the field to examine the object of study and conduct direct interaction with the community. The discussion on the role of the sub-district head in controlling illegal markets in this study is based on the role theory proposed by Biddle and Thomas, which consists of expectations, norms, forms of behavior, as well as assessments and sanctions. The Camat has an important role in regulating various activities carried out by the community, including regulating the market so that the existence of the market does not cause problems for other community groups.